Local hyperexcitability of C-nociceptors may predict responsiveness to topical lidocaine in neuropathic pain - Landmann, Gunther; Stockinger, Lenka; Gerber, Benjamin; Benrath, Justus; Schmelz, Martin; Rukwied, Roman (PLOS ONE, 2022)
We explored whether increased C-nociceptor excitability predicts analgesic effects of topical lidocaine in 33 patients with mono- (n = 15) or poly-neuropathy (n = 18). Excitability of C-nociceptors was tested by transcutaneous electrical sinusoidal (4 Hz) and half sine wave (single 500 ms pulse) stimulation delivered to affected and non-affected sites. Analgesic effects of 24 hrs topical lidocaine were recorded. About 50% of patients reported increased pain from symptomatic skin upon continuous 4 Hz sinusoidal and about 25% upon 500 ms half sine wave stimulation. Electrically-evoked half sine wave pain correlated to their clinical pain level (r = 0.37, p < 0.05). Lidocaine-patches reduced spontaneous pain by >1-point NRS in 8 of 28 patients (p < 0.0001, ANOVA). Patients with increased pain to 2.5 sec sinusoidal stimulation at 0.2 and 0.4 mA intensity had significantly stronger analgesic effects of lidocaine and in reverse, patients with a pain reduction of >1 NRS had significantly higher pain ratings to continuous 1 min supra-threshold sinusoidal stimulation. In the assessed control skin areas of the patients, enhanced pain upon 1 min 4 Hz stimulation correlated to increased depression scores (HADS). Electrically assessed C-nociceptor excitability identified by slowly depolarizing electrical stimuli might reflect the source of neuropathic pain in some patients and can be useful for patient stratification to predict potential success of topical analgesics. Central neuronal circuitry assessment reflected by increased pain in control skin associated with higher HADS scores suggest central sensitization phenomena in a sub-population of neuropathic pain patients.